Development of E-Module-Based PjBL to Develop Computational Thinking Skills Integrategration with CCR Implementation in Science Education - Ulfa, Efrika Marsya; Wahyuni, Sri; Ridlo, Zainur Rasyid (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Objective: This research aims to describe the Validity, Practicality and effectiveness of E-Module. Methods: The research conducted using the type of development research using the ADDIE model was carried out at MTs Negeri 1 Jember. Result: This research develop E-Modul based PjBL. Validity obtained a percentage of 94% and belongs to the category of very valid. The practicality of obtaining a percentage of 97% is included in the excellent category. Effectiveness analysis based on the results of pretest and posttest calculations obtained an N-gain value of 0.57 which is included in the moderate category. The result of student response was 89.7% which was included in the very positive category. So, it can be concluded, the project-based E-Module based on learning business materials and simple machine is effective and can be used in science learning in junior high schools.